Chitosan Gingival Mask Based on Guava Leaf Extract To Prevent Smoker’s Melanosis - Rezmelia Sari; Lutfia Nur Sabrina; Efrin Qorina; Aulia Nathaniela Farin (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Smoker’s melanosis is a common periodontal condition characterized by gingival hyperpigmentation due to excessive tyrosinase activity, which affects aesthetics. Guava leaves contain flavonoids, vitamin C, and coumarin, which have been shown to inhibit pigmentation in the skin and hair. Mucoadhesive films made from chitosan shrimp shell waste are biodegradable and have been proven to be effective as drug delivery systems. This literature review aims to establish a theoretical foundation for the potential combination of guava leaf extract and shrimp waste chitosan as a gingival mask for preventing smoker's melanosis. Literature was systematically compiled from Scopus, ScienceDirect, PubMed, and SAGE, from 2014 to 2024. Inclusion and exclusion criteria were used to formulate a theoretical foundation. Review: The literature shows that flavonoids in guava leaves inhibit ORAI1 calcium channels, vitamin C blocks copper ion bonds, and coumarin prevents the formation of ROS. These mechanisms play crucial roles in inhibiting tyrosinase. Chitosan Mucoadhesive patches with vitamin C solvent enhance the biocompatibility and effectiveness of active substance delivery. Conclusion: The chitosan–guava leaf gingival mask holds potential for preventing smoker’s melanosis through targeted tyrosinase inhibition. Further research is required to optimize the potential of combining guava leaf extract and shrimp waste chitosan for use as a gingival mask.